Erythromycin reduces nasal inflammation by inhibiting immunoglobulin production, attenuating mucus secretion, and modulating cytokine expression - Yen, Ting-Ting; Jiang, Rong-San; Chang, Ching-Yun; Wu, Chih-Ying; Liang, Kai-Li (Scientific reports, 2021)
Allergic rhinitis (AR) and chronic rhinosinusitis (CRS) share some similar pathological mechanisms. In current study, we intend to investigate the impact of AR on CRS. In addition, we explored the efficacy of erythromycin (EM) treatment on CRS mice with or without AR (CRSwoAR, CRSwAR). Study subjects were divided into control, CRSwoAR, and CRSwAR groups. Experimental mice were divided similarly into control, CRSwoAR, and CRSwAR groups. In addition, CRS mice were treated with EM at 0.75, 7.5, or 75 mg/kg or with dexamethasone (Dex) at 1 mg/kg. In our results, allergy exacerbates inflammation that was evident in nasal histology and cytokine expression both in patients and in mice with CRS. Dex 1 mg/kg, EM 7.5 or 75 mg/kg treatments significantly inhibited serum IgE and IgG2a in CRS mice. EM-treated CRS mice had significantly elevated IL-10 levels and had a reversal of Th-1/Th-2 cytokine expression in nasal-associated lymphoid tissue. MUC5AC expressions were significantly reduced in the 7.5 or 75 mg/kg EM-treated mice compared with untreated mice. EM showed inhibitions on immunoglobulin production and mucus secretion stronger than Dex. We concluded that comorbid AR enhanced inflammation of CRS. EM and Dex treatments showed similar anti-inflammatory effects on CRS but through partly different mechanisms.